2019
DOI: 10.5334/ijic.4184
|View full text |Cite
|
Sign up to set email alerts
|

Professional Role Identity: At the Heart of Medical Collaboration Across Organisational Boundaries

Abstract: Purpose: The purpose of this paper was to help answer two persistent calls in the literature: the first asks to strengthen the understanding of medical collaboration across levels of healthcare delivery; the second one requests paying more attention to the individual experience of different forms of professional work. Accordingly, the study was guided by the following research question: How do family physicians and specialists working at different levels of healthcare delivery enact their professi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…Team effectiveness is associated with processes such as work role performance (i.e. actions and behaviors of team members involved in executing tasks) [17,18], professional autonomy [19], team collaboration [20], and decision-making [21]. A recent study found that combinations of different organizational cultures were associated with higher levels of perceived integrated care among patients [22].…”
Section: Research and Theorymentioning
confidence: 99%
“…Team effectiveness is associated with processes such as work role performance (i.e. actions and behaviors of team members involved in executing tasks) [17,18], professional autonomy [19], team collaboration [20], and decision-making [21]. A recent study found that combinations of different organizational cultures were associated with higher levels of perceived integrated care among patients [22].…”
Section: Research and Theorymentioning
confidence: 99%
“…To successfully test new economic and social methods for improving patient management during pregnancy and early motherhood, especially for women in precarious situations, we need to proactively encourage buy-in from the professionals who will deliver these interventions. It may be possible to accomplish this by shifting managerial paradigms (33) or by developing new health organizations, by rede ning the roles of health professionals and patients, and by co-constructing an adapted follow-up procedure (34,35). Health professionals may need to be convinced that recipients experience nancial incentives as a redistribution of wealth to those who need it and not as a stigma.…”
Section: Discussionmentioning
confidence: 99%
“…e rise of care planning due to the increased prevalence of complex and chronic diseases has led to the increasing role of FPs in multidisciplinary care. 14,15 It is essential to ensure that everyone in the team understands each other's scope of practice, strengths and experiences. is requires sharing of power, trust and self-awareness.…”
Section: Mr J's Kawa Modelmentioning
confidence: 99%